Laminate, negative electrode current collector for lithium ion secondary battery, and negative electrode for lithium ion secondary battery

A laminate structure with a copper-nickel composite current collector, optimized for tensile strength through controlled crystallinity, addresses the issue of deformation and cracking in lithium ion secondary batteries, enhancing durability and reliability.

JP7607674B2Active Publication Date: 2024-12-27TDK CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022572180
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-25
Filing Date
2021-12-13
Publication Date
2024-12-27
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

The negative electrode current collector in lithium ion secondary batteries is susceptible to deformation and cracking due to repeated tensile stress caused by the volume changes of the active material layer during charging and discharging, leading to potential short circuits and reduced durability.

Method used

A laminate structure comprising a copper-based first metal layer and a nickel-based second metal layer with controlled crystallinity, where the full width at half maximum of the X-ray diffraction peak from the nickel layer is between 0.3° and 1.2°, enhancing tensile strength through optimized grain boundary management.

Benefits of technology

The laminate structure provides high tensile strength, preventing cracking and deformation of the current collector, thereby improving the durability and reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607674000002
    Figure 0007607674000002
  • Figure 0007607674000003
    Figure 0007607674000003
  • Figure 0007607674000004
    Figure 0007607674000004
Patent Text Reader

Abstract

This multilayer body contains: a first metal layer that contains copper; and a second metal layer that contains nickel, while being directly superposed on the first metal layer. The full width at half maximum of the X-ray diffraction peak having the maximum intensity among at least one X-ray diffraction peak associated with a crystal that contains nickel in the second metal layer is from 0.3° to 1.2°.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate, a negative electrode current collector for a lithium ion secondary battery, and a negative electrode for a lithium ion secondary battery. [Background technology]

[0002] A negative electrode current collector for a lithium-ion secondary battery is subjected to repeated loads (compressive stress and tensile stress) due to the volume of the negative electrode active material layer laminated on the negative electrode current collector fluctuating with charging and discharging. Deformation of the negative electrode current collector due to this load causes deformation of the battery body or short-circuiting between electrodes. Therefore, the negative electrode current collector is required to have durability (high tensile strength) against loads (especially tensile stress) (see Patent Document 1 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2005-197205 A Summary of the Invention [Problem to be solved by the invention]

[0004] When a metal layer such as a current collector is subjected to tensile stress, cracks form in the metal layer due to slippage of crystal grain boundaries in the metal layer, and the cracks expand. As a result, the metal layer breaks. When the metal layer is made of an amorphous iron-based alloy with low crystallinity, the metal layer tends to have high tensile resistance. However, the inventors have found that high tensile strength is not necessarily obtained even if the metal layer is amorphous, and that high tensile strength is obtained when the metal layer has a certain degree of crystallinity.

[0005] An object of one aspect of the present invention is to provide a laminate having high tensile strength, and a negative electrode current collector and a negative electrode for a lithium ion secondary battery including the laminate. [Means for solving the problem]

[0006] A laminate according to one aspect of the present invention includes a first metal layer containing copper, and a second metal layer containing nickel and directly laminated on the first metal layer, wherein the full width at half maximum of at least one X-ray diffraction peak having the maximum intensity among at least one X-ray diffraction peak derived from a crystal containing nickel in the second metal layer is 0.3° or more and 1.2° or less.

[0007] The second metal layer may further include at least one element selected from the group consisting of carbon, phosphorus, and tungsten.

[0008] A negative electrode current collector for a lithium ion secondary battery according to one aspect of the present invention includes the above laminate.

[0009] A negative electrode for a lithium ion secondary battery according to one aspect of the present invention includes the above-described negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, in which the negative electrode active material layer is laminated directly on the second metal layer.

[0010] The negative electrode active material may contain silicon. Effect of the Invention

[0011] According to one aspect of the present invention, there is provided a laminate having high tensile strength, and a negative electrode current collector and a negative electrode for a lithium ion secondary battery including the laminate. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic perspective view of a laminate (negative electrode current collector) according to one embodiment of the present invention, and a negative electrode including the laminate. [Diagram 2] FIG. 2 is an example of an X-ray diffraction pattern measured by irradiating X-rays on the surface of the second metal layer in the laminate. [Diagram 3] FIG. 3 is an enlarged view of FIG. 2, and shows an example of an X-ray diffraction peak (X-ray diffraction peak with maximum intensity) derived from crystals containing nickel in the second metal layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. In the drawings, the same components are designated by the same reference numerals. The present invention is not limited to the following embodiments.

[0014] The laminate according to this embodiment is a negative electrode current collector for a lithium ion secondary battery. As shown in FIG. 1, the laminate 10 according to this embodiment has a first metal layer 1 and a second metal layer 2. The first metal layer 1 contains copper (Cu). The second metal layer 2 contains nickel (Ni). In the case of the laminate 10 shown in FIG. 1, the second metal layer 2 is directly laminated on both surfaces of the first metal layer 1. However, the second metal layer 2 may be directly laminated on only one surface of the first metal layer 1.

[0015] 1, the negative electrode 20 for a lithium ion secondary battery according to this embodiment has a laminate 10 (negative electrode current collector) and a negative electrode active material layer 3. The negative electrode active material layer 3 contains a negative electrode active material. The negative electrode active material layer 3 is laminated directly on the surface of each second metal layer 2. The lithium ion secondary battery according to this embodiment may include a negative electrode 20, a positive electrode, a separator, and an electrolyte. The separator and the electrolyte are disposed between the negative electrode 20 and the positive electrode. The electrolyte permeates the separator. The positive electrode may include a positive electrode current collector and a positive electrode active material layer laminated on the positive electrode current collector. For example, the positive electrode current collector may be an aluminum foil or a nickel foil. The positive electrode active material layer includes a positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), LiNi x Co y Mn z M aO2 (x + y + z + a = 1, 0 ≤ x < 1, 0 ≤ y < 1, 0 ≤ z < 1, 0 ≤ a < 1, M is one or more elements selected from the group consisting of Al, Mg, Nb, Ti, Cu, Zn, and Cr), lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (M is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, and Zr, or VO), lithium titanate (Li4Ti5O 12 )、LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1), which may be one or more compounds selected from the group consisting of polyacetylene, polyaniline, polypyrrole, polythiophene, and polyacene. The positive electrode active material layer may further contain a conductive assistant such as carbon or metal powder. The positive electrode active material layer may further contain a binder (adhesive or resin). The separator may be one or more films (films or laminates) made of a porous polymer having electrical insulation. The electrolyte contains a solvent and an electrolyte (lithium salt). The solvent may be water or an organic solvent. For example, the electrolyte (lithium salt) may be one or more lithium compounds selected from the group consisting of LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, and LiBOB.

[0016] At least one X-ray diffraction peak P having the maximum intensity among the X-ray diffraction peaks derived from the crystals containing Ni in the second metal layer 2 MAX has a full width at half maximum of 0.3° or more and 1.2° or less. The full width at half maximum of the X-ray diffraction peak P MAX being 0.3° or more and 1.2° or less enables the laminate 10 to have high tensile strength. The tensile strength means the durability of the laminate 10 against the tensile stress in the direction parallel to the surface of the second metal layer 2. The X-ray diffraction peak P MAXThe mechanism by which the laminate 10 has high tensile strength when the full width at half maximum is 0.3° or more and 1.2° or less is as follows. However, the following mechanism is hypothetical, and the technical scope of the present invention is not limited by the following mechanism.

[0017] Since the laminate 10 has not only the first metal layer 1 but also the second metal layer 2 laminated on the first metal layer 1, the laminate 10 can have a higher tensile strength than a conventional current collector consisting of only one metal layer containing Cu. However, the high tensile strength of the laminate 10 is due not only to the laminate structure but also to the crystallinity of the second metal layer 2. The second metal layer 2 includes a large number of crystal grains containing Ni. MAX As the full width at half maximum of the X-ray diffraction peak P decreases, the grain size of each crystal grain in the second metal layer 2 increases, and the crystallinity of the second metal layer 2 increases. MAX When the full width at half maximum of the X-ray diffraction peak P is too small, each crystal grain is too large, and the area of ​​the grain boundary between a pair of adjacent crystal grains is too wide. As a result, due to the tensile stress received by the second metal layer 2, large cracks are likely to form all at once along the wide grain boundaries, and the cracks are likely to propagate (grow) into the second metal layer 2, and the second metal layer 2 and the entire laminate 10 are likely to break. However, when the X-ray diffraction peak P MAX When the full width at half maximum of the X-ray diffraction peak P is 0.3° or more, the propagation (growth) of cracks caused by excessively large crystal grains (high crystallinity) is suppressed, and the entire laminate 10 including the second metal layer 2 can have high tensile strength. MAX When the full width at half maximum of is 0.3° or more, the crystal grains are appropriately refined and the area of ​​the grain boundaries is appropriately small, so that the propagation of cracks along the grain boundaries is suppressed. X-ray diffraction peak P MAX With an increase in the full width at half maximum of the X-ray diffraction peak P, the grain size of each crystal grain in the second metal layer 2 decreases, and the crystallinity of the second metal layer 2 decreases. MAX As the full width at half maximum of the X-ray diffraction peak P MAXWhen the full width at half maximum of the X-ray diffraction peak P is too large, each crystal grain is too fine, and many fine grain boundaries are formed in the second metal layer 2. As a result, due to the tensile stress received by the second metal layer 2, cracks tend to propagate (grow) linearly in the second metal layer 2 along paths formed by many fine grain boundaries, and the second metal layer 2 and the entire laminate 10 tend to break. However, MAX When the full width at half maximum of the X-ray diffraction peak P is 1.2° or less, cracks caused by fine crystal grains (low crystallinity) are suppressed, and the entire laminate 10 including the second metal layer 2 can have high tensile strength. MAX When the full width at half maximum of is 1.2° or less, the propagation of a crack along a grain boundary is likely to be interrupted by moderately large crystal grains, and the direction of the crack propagation is likely to be changed by moderately large crystal grains, so that linear crack propagation is suppressed. The tensile strength of the laminate 10 may be, for example, 800 MPa or more and 1300 MPa or less, 890 MPa or more and 1200 MPa or less, 897 MPa or more and 1200 MPa or less, 1000 MPa or more and 1200 MPa or less, or 1006 MPa or more and 1200 MPa or less.

[0018] Since the laminate 10 tends to have high tensile strength, the X-ray diffraction peak P MAX The full width at half maximum may be 0.36° or more and 1.06° or less, 0.37° or more and 1.06° or less, or 0.39° or more and 1.06° or less.

[0019] At least one X-ray diffraction peak resulting from the Ni-containing crystals in the second metal layer 2 is included in an X-ray diffraction pattern measured by irradiating X-rays on the surface of the second metal layer 2. An example of an X-ray diffraction pattern is shown in Fig. 2. Fig. 3 is an enlarged view of Fig. 2, and shows the maximum X-ray diffraction peak P MAX2 and 3, the X-ray diffraction pattern may include, in addition to the X-ray diffraction peak derived from the crystal containing Ni, at least one X-ray diffraction peak derived from the crystal containing Cu in the first metal layer 1. Among the multiple X-ray diffraction peaks included in the X-ray diffraction pattern, the number of X-ray diffraction peaks derived from the crystal containing Ni may be one or more. The X-ray diffraction peak derived from the crystal containing Ni may be distinguished from the X-ray diffraction peak derived from the crystal containing Ni based on the diffraction angle 2θ.

[0020] The Ni-containing crystal in the second metal layer 2 may have a face-centered cubic (fcc) structure. Among at least one X-ray diffraction peak derived from the Ni-containing crystal in the second metal layer 2, the X-ray diffraction peak P MAX may be an X-ray diffraction peak derived from one crystal plane selected from the group consisting of the (111) plane, the (200) plane, and the (220) plane among the crystal planes of the face-centered cubic structure. The Ni-containing crystal in the second metal layer 2 may be a crystal consisting of Ni only. As long as the face-centered cubic structure of the Ni-containing crystal is maintained, the Ni-containing crystal may further contain an element other than Ni. X-ray diffraction peak P MAX The diffraction angle 2θ may vary depending on the wavelength of the incident X-ray, the composition of the crystal, and the lattice constant, and is not particularly limited.

[0021] Ni may be the main component of the second metal layer 2. In other words, when the second metal layer 2 contains a plurality of elements, the Ni content (unit: mass%) may be the largest. The Ni content in the second metal layer 2 may be, for example, 60 mass% or more and 100 mass% or less, 60 mass% or more and less than 100 mass%, or 60 mass% or more and 99.5 mass% or less. When the second metal layer 2 contains three or more elements, the Ni content in the second metal layer 2 may be less than 50 mass%. At least a part or the whole of the second metal layer 2 may be simple Ni, an alloy containing Ni, or an intermetallic compound containing Ni.

[0022] The second metal layer 2 may further contain at least one element selected from the group consisting of carbon (C), phosphorus (P) and tungsten (W). By containing these elements in the second metal layer 2, the X-ray diffraction peak P MAX For example, when the second metal layer 2 contains C, the grain size of the crystals containing Ni is reduced, and the X-ray diffraction peak P MAX The full width at half maximum of the Ni-containing crystal in the second metal layer 2 may further contain at least one element selected from the group consisting of C, P, and W. For example, the Ni-containing crystal in the second metal layer 2 may be a solid solution containing at least one element selected from the group consisting of C, P, and W.

[0023] The second metal layer 2 may be formed by electrolytic plating or electroless plating. As shown in the examples described later, when the electrolytic plating or electroless plating is used, the X-ray diffraction peak P MAX It is possible to control the full width at half maximum of the X-ray diffraction peak P MAX The factors controlling the full width at half maximum of the X-ray diffraction peak P may be the composition of the plating solution, the concentration of the raw material (a compound containing Ni) in the plating solution, the temperature of the plating solution, the pH of the plating solution, the current density of the first metal layer 1, and the plating time. MAX The full width at half maximum of the may be adjusted.

[0024] Cu may be the main component of the first metal layer 1. The first metal layer 1 may consist only of Cu. The first metal layer 1 may consist of an alloy containing Cu. When the first metal layer 1 contains Cu, the laminate 10 can have high conductivity required for a negative electrode current collector for a lithium ion secondary battery.

[0025] The negative electrode active material contained in the negative electrode active material layer 3 is not particularly limited as long as it is a material capable of absorbing and releasing lithium ions. For example, the negative electrode active material contained in the negative electrode active material layer 3 may contain silicon (Si). A negative electrode active material containing silicon is more likely to expand and contract with charging and discharging of a lithium ion secondary battery than other negative electrode active materials. Due to the change in volume of the negative electrode active material layer 3 with charging and discharging, the laminate 10 (second metal layer 2) is subjected to repeated tensile stress. However, since the laminate 10 according to this embodiment has high tensile strength, breakage of the laminate 10 caused by the change in volume of the negative electrode active material layer 3 is suppressed.

[0026] The negative electrode active material containing silicon may be a simple substance of silicon, an alloy containing silicon, or a compound containing silicon (such as an oxide or silicate). For example, the alloy containing silicon may contain at least one element selected from the group consisting of tin (Sn), nickel (Ni), copper (Cu), iron (Fe), cobalt (Co), manganese (Mn), zinc (Zn), indium (In), silver (Ag), titanium (Ti), germanium (Ge), bismuth (Bi), antimony (Sb) and chromium (Cr). For example, the compound containing silicon may contain at least one element selected from the group consisting of boron (B), nitrogen (N), oxygen (O) and carbon (C). For example, negative electrode active materials containing silicon include SiB4, SiB6, Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, NbSi2, TaSi2, VSi2, WSi2, ZnSi2, SiC, Si2N2, Si2N2O, SiO XIt may be at least one compound selected from the group consisting of (0 < X ≦ 2) and LiSiO. The negative electrode active material may be a silicon-containing fiber (such as a nanowire) or a silicon-containing particle (such as a nanoparticle). The negative electrode active material layer 3 may further contain a binder. The binder binds the negative electrode active materials to each other and binds the negative electrode active material layer 3 to the surface of the second metal layer 2.

[0027] The thickness T1 of the first metal layer 1 may be, for example, 1 μm or more and 8 μm or less. The thickness T2 of one second metal layer 2 may be, for example, 0.3 μm or more and 4 μm or less, or 1.1 μm or more and 2.0 μm or less. The total thickness of the second metal layers 2 is represented as T2 TOTAL and may be, and T2 TOTAL / T1 may be 0.6 or more and 1.0 or less. For example, as shown in FIG. 1, when the laminate 10 has two second metal layers 2, T2 TOTAL is the sum of the thicknesses of the two second metal layers 2. T2 TOTAL When T2 / T1 is 0.6 or more, the laminate 10 is likely to have a sufficiently high tensile strength. The smaller T2 TOTAL / T1 is, the cost of the raw material of the laminate 10 (second metal layer 2) is suppressed. When T2 TOTAL / T1 is 1.0 or less, the lithium-ion secondary battery including the laminate 10 is likely to have a sufficiently high energy density. The thickness T3 of one negative electrode active material layer 3 may be, for example, 10 μm or more and 300 μm or less. The thicknesses T1 of the first metal layer 1, T2 of the second metal layer 2, and T3 of the negative electrode active material layer 3 may each be uniform.

[0028] The dimensions of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be substantially the same as each other. For example, the width of each of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be several tens of mm or more and several hundreds of mm or less. The length of each of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be several tens of mm or more and several thousands of mm or less.

[0029] The present invention is not necessarily limited to the above-described embodiment. Various modifications of the present invention are possible without departing from the spirit of the present invention, and these modifications are also included in the present invention.

[0030] For example, the second metal layer may be formed by a vapor deposition process such as sputtering, metalorganic chemical vapor deposition (MOCVD), or metalorganic physical vapor deposition (MOPVD).

[0031] The laminate according to the present invention may be used as a heat dissipation material or an electromagnetic wave shielding material. Tensile stress acts on the heat dissipation material or the electromagnetic wave shielding material during processing. Since the laminate according to the present invention has high tensile strength, damage to the heat dissipation material or the electromagnetic wave shielding material during processing can be suppressed. EXAMPLES

[0032] The present invention will be described in detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.

[0033] [Pretreatment of the first metal layer] A commercially available electrolytic copper foil was used as the first metal layer. The thickness of the first metal layer was 4.5 μm. The thickness of the first metal layer was uniform. The first metal layer was immersed in an acidic degreasing solution for 1 minute to remove organic matter adhering to the surface of the first metal layer. As the degreasing solution, Thru-cup MSC-3-A manufactured by Uemura Kogyo Co., Ltd. was used. After degreasing, the first metal layer was cleaned by immersing it in pure water for 1 minute.

[0034] After the first metal layer was washed, the first metal layer was immersed in dilute sulfuric acid for 1 minute to remove the native oxide film present on the surface of the first metal layer. The concentration of the dilute sulfuric acid was 10 mass %. After the native oxide film was removed, the first metal layer was washed by immersing it in pure water for 1 minute.

[0035] Using the first metal layer that had been subjected to the above pretreatment, laminates of Examples 1 to 10 and Comparative Examples 1 to 4 were produced by the following method.

[0036] Example 1 The second metal layer was formed on both surfaces of the first metal layer by the following electrolytic plating, i.e., a laminate was formed by the electrolytic plating, which was composed of the first metal layer and the second metal layer laminated on both surfaces of the first metal layer. In the electrolytic plating, the second metal layer and the other electrodes connected to a power source were immersed in a plating solution, and a current was applied to the second metal layer and the other electrodes. The plating solution contained nickel sulfate hexahydrate, sodium tungstate dihydrate, and trisodium citrate. The content of nickel sulfate hexahydrate in the plating solution was 60 g / L. The content of sodium tungstate dihydrate in the plating solution was 100 g / L. The content of trisodium citrate in the plating solution was 145 g / L. The pH of the plating solution was adjusted to 5.0. The temperature of the plating solution was adjusted to 50° C. The current density of the first metal layer during electrolytic plating was 5 A / dm 2 The duration of electrolytic plating was 1 min.

[0037] After electrolytic plating, the laminate was washed by immersing it in pure water for 1 minute. After washing the laminate, moisture adhering to the laminate was removed. After removing the moisture, the laminate was heat-treated at 110°C for 6 hours.

[0038] By the above method, the laminate of Example 1 was produced.

[0039] Example 2 The duration of electrolytic plating was 1.5 minutes in Example 2. The laminate of Example 2 was produced in the same manner as in Example 1, except for the duration of electrolytic plating.

[0040] Example 3 In the case of Example 3, the second metal layer was formed on both surfaces of the first metal layer by the following electroless plating rather than electrolytic plating.

[0041] A catalytic treatment of the first metal layer was carried out before electroless plating. In the catalytic treatment, the first metal layer was immersed in a catalytic treatment solution for one minute to attach a catalyst (palladium sulfate) to the surface of the first metal layer. The temperature of the catalytic treatment solution was adjusted to 40°C. Axmalta MNK-4-M manufactured by Uemura Kogyo Co., Ltd. was used as the catalytic treatment solution.

[0042] In the electroless plating, the first metal layer that had been subjected to the catalytic treatment was immersed in an electroless nickel plating solution for 1 minute. The electroless nickel plating solution contained sodium hypophosphite as a reducing agent. The temperature of the electroless nickel plating solution was adjusted to 90°C. The duration of the electroless plating was 7 minutes. Nimden KLP manufactured by Uemura Kogyo Co., Ltd. was used as the electroless nickel plating solution.

[0043] By the above method, the laminate of Example 3 was produced.

[0044] Example 4 The duration of electroless plating was 10 minutes in Example 4. The laminate of Example 4 was produced in the same manner as in Example 3, except for the duration of electroless plating.

[0045] Example 5 The electrolytic plating of Example 5 was carried out using a plating solution having a different composition from that of Example 1. The plating solution of Example 5 contained nickel sulfate hexahydrate, nickel chloride hexahydrate, boric acid, and sodium saccharin. The content of nickel sulfate hexahydrate in the plating solution of Example 5 was 240 g / L. The content of nickel chloride hexahydrate in the plating solution of Example 5 was 45 g / L. The content of boric acid in the plating solution of Example 5 was 30 g / L. The content of sodium saccharin in the plating solution of Example 5 was 2 g / L. The pH of the plating solution of Example 5 was adjusted to 4.2. The temperature of the plating solution of Example 5 was adjusted to 40° C. The duration of the electrolytic plating of Example 5 was 1.5 minutes.

[0046] A laminate of Example 5 was produced in the same manner as in Example 1, except for the above points.

[0047] Example 6 The duration of electrolytic plating was 2 minutes in Example 6. The laminate of Example 6 was produced in the same manner as in Example 5, except for the duration of electrolytic plating.

[0048] Example 7 The content of sodium tungstate dihydrate in the plating solution of Example 7 was 30 g / L. The content of trisodium citrate in the plating solution of Example 7 was 80 g / L. The pH of the plating solution of Example 7 was adjusted to 7.0. The duration of electrolytic plating of Example 7 was 4 minutes. A laminate of Example 7 was produced in the same manner as in Example 1, except for the above-mentioned points.

[0049] Example 8 The content of nickel sulfate hexahydrate in the plating solution of Example 8 was 70 g / L. The content of sodium tungstate dihydrate in the plating solution of Example 8 was 15 g / L. The content of trisodium citrate in the plating solution of Example 8 was 80 g / L. The pH of the plating solution of Example 8 was adjusted to 7.0. The duration of electrolytic plating of Example 8 was 3 minutes. A laminate of Example 8 was produced in the same manner as in Example 1, except for the above-mentioned points.

[0050] Example 9 The content of nickel sulfate hexahydrate in the plating solution of Example 9 was 75 g / L. The content of sodium tungstate dihydrate in the plating solution of Example 9 was 8 g / L. The content of trisodium citrate in the plating solution of Example 9 was 80 g / L. The pH of the plating solution of Example 9 was adjusted to 7.0. The duration of electrolytic plating of Example 9 was 3 minutes. A laminate of Example 9 was produced in the same manner as in Example 1, except for the above-mentioned points.

[0051] Example 10 The content of nickel sulfate hexahydrate in the plating solution of Example 10 was 80 g / L. The content of sodium tungstate dihydrate in the plating solution of Example 10 was 4 g / L. The content of trisodium citrate in the plating solution of Example 10 was 80 g / L. The pH of the plating solution of Example 10 was adjusted to 7.0. The duration of electrolytic plating of Example 10 was 3 minutes. A laminate of Example 10 was produced in the same manner as in Example 1, except for the above-mentioned points.

[0052] Comparative Example 1 The plating solution of Comparative Example 1 did not contain sodium saccharin. The laminate of Comparative Example 1 was produced in the same manner as in Example 5, except that the plating solution did not contain sodium saccharin.

[0053] Comparative Example 2 The duration of electrolytic plating was 2 minutes in Comparative Example 2. The laminate of Comparative Example 2 was produced in the same manner as in Comparative Example 1, except for the duration of electrolytic plating.

[0054] Comparative Example 3 Electroless plating in Comparative Example 3 was performed using an electroless nickel plating solution having a different composition from that of Example 3. The content of sodium hypophosphite in the electroless nickel plating solution of Comparative Example 3 was greater than that of sodium hypophosphite in the electroless nickel plating solution of Example 3. ICP Nicoron SOF manufactured by Okuno Chemical Industries Co., Ltd. was used as the electroless nickel plating solution of Comparative Example 3. The temperature of the electroless nickel plating solution of Comparative Example 3 was adjusted to 85°C.

[0055] A laminate of Comparative Example 3 was produced in the same manner as in Example 3, except for the above points.

[0056] Comparative Example 4 The duration of electroless plating was 10 minutes in Comparative Example 4. The laminate of Comparative Example 4 was produced in the same manner as in Comparative Example 3, except for the duration of electroless plating.

[0057] [Laminate analysis] The laminates of Examples 1 to 10 and Comparative Examples 1 to 4 were analyzed by the following method.

[0058] The laminate was cut in the lamination direction (direction perpendicular to the surface of the second metal layer), and the cross section of the laminate was observed with a scanning electron microscope (SEM).

[0059] The composition of the second metal layer exposed on the cross section of the laminate was analyzed by energy dispersive X-ray spectroscopy (EDS). It was confirmed that the second metal layer of each of Examples 1 to 10 and Comparative Examples 1 to 4 contained the constituent elements shown in Table 1 below. The Ni content in the second metal layer of each of Examples 1 to 10 and Comparative Examples 1 to 4 is shown in Table 1 below.

[0060] In all of Examples 1 to 10 and Comparative Examples 1 to 4, the thickness of each of the second metal layers laminated on both surfaces of the first metal layer was uniform. The thickness of the second metal layer was measured on the cross section of the laminate. The thickness T2 of the second metal layer is shown in Table 1 below. The sum T2 of the thicknesses T2 of the two second metal layers 2 is TOTAL are also shown in Table 1 below.

[0061] The X-ray diffraction pattern was measured by irradiating the surface of the second metal layer of the laminate with X-rays. CuKα rays were used as the incident X-rays.

[0062] In all of Examples 1 to 10 and Comparative Examples 1 and 2, at least one X-ray diffraction peak derived from Ni crystals in the second metal layer was included in the X-ray diffraction pattern. On the other hand, in the cases of Comparative Examples 3 and 4, no clear X-ray diffraction peak derived from Ni crystals in the second metal layer was detected. Therefore, it was inferred that the second metal layers in each of Comparative Examples 3 and 4 were amorphous.

[0063] In the cases of Examples 1 to 10 and Comparative Examples 1 and 2, the X-ray diffraction peak P MAXThe full width at half maximum of is shown in the following Table 1. In all of Examples 1 to 10 and Comparative Examples 1 and 2, the X-ray diffraction peak P MAX was an X-ray diffraction peak originating from the (111) plane of a Ni crystal (face-centered cubic structure).

[0064] The X-ray diffraction pattern of Example 4 is shown in FIG. MAX is shown in FIG.

[0065] [Tensile test] The following tensile test was performed using a load tester to measure the tensile strength of each of the laminates in Examples 1 to 10 and Comparative Examples 1 to 4. The load tester used was FTN1-13A manufactured by Aikoh Engineering Co., Ltd.

[0066] Test specimens were prepared by punching the laminate in the lamination direction. The shape of the test specimen was dumbbell-shaped. Tension was applied to the test specimen and gradually increased until the test specimen broke. The maximum tension (unit: N) just before the test specimen broke was calculated as a function of the cross-sectional area (unit: m 2 The tensile strength (unit: MPa) is calculated by dividing the tensile strength by the average strength (MPa) of the specimen. The tensile strengths of Examples 1 to 10 and Comparative Examples 1 to 4 are shown in Table 1 below.

[0067] [Table 1] [Industrial Applicability]

[0068] For example, the laminate according to one aspect of the present invention may be used as a negative electrode current collector of a lithium ion secondary battery. [Explanation of symbols]

[0069] 1...first metal layer, 2...second metal layer, 3...negative electrode active material layer, 10...laminated body (current collector), 20...negative electrode.

Claims

1. A negative electrode current collector for a lithium ion secondary battery comprising a laminate, The laminate comprises: a first metal layer comprising copper; a second metal layer comprising nickel and laminated directly to the first metal layer; Equipped with the full width at half maximum of an X-ray diffraction peak having the maximum intensity among at least one X-ray diffraction peak derived from nickel-containing crystals in the second metal layer is 0.3° or more and 1.2° or less; the crystal containing nickel has a face-centered cubic structure, the X-ray diffraction peak having the maximum intensity is derived from a (111) plane of the face-centered cubic structure, The second metal layer further contains at least one element selected from the group consisting of carbon, phosphorus, and tungsten. Negative electrode current collector for lithium-ion secondary batteries.

2. The negative electrode current collector according to claim 1 ; a negative electrode active material layer including a negative electrode active material; Equipped with The negative electrode active material layer is directly laminated to the second metal layer. A negative electrode for lithium-ion secondary batteries.

3. The negative electrode active material contains silicon. The negative electrode according to claim 2 .

Citation Information

Patent Citations

  • Carrier foil-fitted porous metal foil and its production method

    JP2005320562A

  • JP2005‐197205A

  • Electrode for lithium secondary battery

    JP2011146131A

  • Conductive member, and its production method

    JP2019026941A

  • Multilayer material and production method thereof, and multilayer material plating method

    JP2021038445A